2012
DOI: 10.1055/s-0038-1625710
|View full text |Cite
|
Sign up to set email alerts
|

Considerações hidrodinâmicas sobre a derivação liquórica V: alterações nos dimensionamentos originais do sistema valvular no momento do implante alteram suas características hidrodinâmicas e induzem a erros de avaliação clínica pelo neurocirurgião

Abstract: Resumo Objetivo: Averiguar se as características hidrodinâmicas das válvulas se alteram significativamente quando os dimensionamentos originais são violados e a possível repercussão clínica desse fato. Métodos: Foi utilizada uma bancada de testes automatizada, conforme a norma ISO 7197. Um sistema valvular foi testado inicialmente com os componentes preconizados e embalados originalmente com o produto. A seguir, substituiu-se o cateter peritoneal original por diversos dimensionamentos encontrados no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In a previous work,[17] we have demonstrated that small changes either in diameter or length of original peritoneal catheters compromise the resistive effect of the shunt assembly. Shunt selection was at random, and we tested adult-type, high- and medium-pressure shunts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous work,[17] we have demonstrated that small changes either in diameter or length of original peritoneal catheters compromise the resistive effect of the shunt assembly. Shunt selection was at random, and we tested adult-type, high- and medium-pressure shunts.…”
Section: Introductionmentioning
confidence: 99%
“…Neurosurgeons routinely cut off pieces of the peritoneal catheter upon shunt implantation/revision, and this occurs more frequently in the pediatric and newborn population due obviously to the height of the patients. In a previous work,[ 17 ] we have demonstrated that small changes either in diameter or length of original peritoneal catheters compromise the resistive effect of the shunt assembly. Shunt selection was at random, and we tested adult-type, high- and medium-pressure shunts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the shunt components can modify the neurological valve pressure class and interfere in the treatment of hydrocephalus. Allin et al (2008), Czosnyka et al (1997Czosnyka et al ( , 2002 and Suriano et al (2012) presented their results with statistical analyses. However, there was no evidence of evaluation of the testing rigs used in the tests or the analysis of experimental uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…Suriano et al (2012), determined the relative pressure-flow rate of a shunt on a testing rig to show that changes to the original diameter and length of the peritoneal catheter, during installation of the implant or surgical revision, change the hydrodynamic behavior of the drainage system and can induce errors in the clinical evaluation of the patient by the neurosurgeon. Changes in the shunt components can modify the neurological valve pressure class and interfere in the treatment of hydrocephalus.…”
Section: Introductionmentioning
confidence: 99%